The founders of the pharmacy in Serbia in the 19th century - Petrović, Bojana; Vukomanović, Predrag (Archives of Pharmacy, 2022)
The founders of modern Serbian pharmacy were certainly the pharmacists Matej Ivanović (1773–1849) and Pavle Ilić (1807-1871). During the 19th century, due to uncertain conditions in Serbia, the development of pharmacy and medicine has stagnated. Such an uncertain situation lasted until the adoption of the famous "Hatisherif" in 1830 when Serbia was recognized as constitutional, gained the status of the principality, political independence, and all governmental institutions were formed. In the same year, 1830, Mateja Ivanović received approval to establish the first modern Serbian pharmacy Prince Miloš and the positive opinion of Dr. Kunibert. The pharmacy was originally built near the Orthodox Cathedral Church in Belgrade. It was important for the supply of medicines, both in the city and for patients from other parts of Serbia. During its existence, the pharmacy changed its location twice. Today, "Pharmacy Mr Matej Ivanović" is part of the “Pharmacy Belgrade”, located on the Knez Mihajlova Street, and is the foundation of modern pharmaceutical service in Serbia. Pavle Ilić is the father of Serbian modern school pharmacy, applied chemistry, and the founder of the state pharmacy in Serbia opened in 1836 in Kragujevac (then the capital of Serbia). After the capital moved to Belgrade in 1841, the pharmacy was moved as well. Today it is called "Pharmacy Macedonia" and is part of the “Pharmacy Belgrade”. In addition to making medicines, Pavle Ilić made an immeasurable contribution to the development of pharmacy by performing toxicological, chemical analyzes, and analyzes of mineral waters.